Downregulation of microRNA-31 inhibits proliferation and induces apoptosis by targeting HIF1AN in human keloid - Zhang, Juan (Oncotarget, 2017)
microRNAs (miRNAs) play a pivotal role in the regulation of cell proliferation and apoptosis in keloid scarring. Integrative analysis of the previous miRNA microarray revealed miRNA-31 was among the most frequently altered miRNAs in keloid and hypertrophic scar. Using qRT-PCR, we further validated miRNA-31 was increased in keloid tissues and keloid-derived fibroblasts. Moreover, downregulation of miRNA-31 inhibited the cell proliferation, induced the cell apoptosis and disturbed the cell cycle progression by targeting HIF1AN, a negative modulator of hypoxia inducible factor 1. Through the luciferase reporter assay, HIF1AN was confirmed to be a target of miRNA-31. Further studies demonstrated that miRNA-31 regulated proliferation, apoptosis and cell cycle of keloid-derived fibroblasts by mediating HIF1AN/VEGF signaling pathway. Overall, our findings shed new light on miRNA-31 as a promising therapeutic target in keloid scarring.